Maize in Eastern and Southern Africa: 'seeds' of success in retrospect - Smale, Melinda; Jayne, Thomas S. (International Food Policy Research Institute, 2003)
This synthesis revisits the “maize success story” in Sub-Saharan Africa, drawing selectively from an extensive published literature about maize seed technical change and related policies. The review focuses on the countries of Kenya, Zimbabwe, Zambia, and Malawi, where maize is most important in the food economy, and refers to the period when maize became a dominant food crop through the 1990s. The term “success” is equivocal in this case, both because of the difficult of establishing the appropriate counterfactual and because some of the policies that contributed to success in one period later led to decline. While the “seeds” themselves were the result of innovative, successful maize breeding, boom periods in maize production were episodic and the public investments in the controlled markets that bolstered them were not fiscally sustainable. Since maize will remain a crucial part of the food security equation even while the agricultural economies of the region diversify, continued investments in both maize research and market institutions, some of which must be public, are essential. The most vital question, however, is where the domestic political pressure to support these investments will originate -- an issue related to governance.